Effects of integrative neuromuscular training and detraining on countermovement jump performance in youth volleyball players - Nunes, A. C.; Cattuzzo, M. T.; Faigenbaum, A. D.; Mortatti, A. L. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to analyze the effect of integrative neuromuscular training (INT) on countermovement vertical jump height (CVJH) performance in youth volleyball players before and after a detraining period. Thirty-two novice volleyball players were cluster randomized into 2 groups: intervention group—INT (age: 13.1 ± 0.4 years; body mass: 55.3 ± 12.1 kg; and height: 161.1 ± 6.4 cm) and control group—CON (age: 12.8 ± 0.7 years; body mass: 51.8 ± 13.6 kg; and height: 160.1 ± 10.7 cm). The subjects were evaluated for somatic maturation (years from peak height velocity) and for CVJH performance at 4 time points during the 20-week study period: baseline, 6 weeks of INT, 12 weeks of INT, and 8 weeks after INT (detraining). The analysis used repeated-measures analysis of variance and Bonferroni post hoc test to identify possible differences in the CVJH delta in both groups. Spearman correlation was performed to verify the association between the values of the vertical jump tests and maturational levels found. The INT showed a significant improvement in the CVJH from baseline to 12 weeks and maintained training-induced gains after detraining period (p > 0.001). Significant increase in CVJH was found in the percentage of change (Delta%) from baseline to 6 weeks (p < 0.005), 12 weeks (p < 0.001), and detraining (p < 0.001) in INT compared with the CON. The results of this study indicate that INT was able to improve CVJH performance in novice youth volleyball players and these gains were sustained during the detraining period. These findings indicate that regular participation in supervised INT can enhance jumping performance in young volleyball players, and that this type of neuromuscular program may be particularly beneficial for youth with limited fundamental motor skill performance.